P087 What is keeping Australian farmers awake at night? Associations between sleep and mental health. (9th November 2022) - Paech, G; Fehlberg, R; Tong, K
Abstract: Introduction: In Australia, suicide rates are higher in farmers compared to the general population. The relationship between poor sleep and mental health is well known, yet there is limited evidence examining Australian farmers' sleep and the role sleep plays in farmers mental health. Therefore, this study investigated the sleep and mental health of Australian farmers using an online questionnaire. Methods: Farmers aged 18 and older (n=101; 52 males) completed a questionnaire (REDCap). The questionnaire included the Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI) and Depression Anxiety Stress Scales (DASS-21). PSQI and ISI scores were split into normal values ('below threshold'; PSQI<5; ISI<8) and abnormal values ('above threshold'). Independent t-tests (Mann-Whitney) were performed to assess differences in mental health between the two threshold groups. Results: Most participants worked full time (89%) on a family farm (70%) and were aged 26-55 (61%). Individuals with PSQI scores above threshold had higher DASS-21 scores across all subscales (p≤0.01; Depression 4.9±3.9; Anxiety 7.6±4.4; Stress 3.8±3.7) compared to those below threshold (Depression 2.9±3.0; Anxiety 5.1±3.2; Stress 1.9±2.0). All DASS-21 subscales scores were also higher in individuals with ISI scores above threshold (p<0.001; Depression 5.0±3.9; Anxiety 7.3±4.2; Stress 3.8±4.1) compared to those below threshold (Depression 2.5±2.9; Anxiety 4.5±3.0; Stress 1.7±1.9). Discussion: Results suggest that Australian farmers who have insomnia symptoms and poor sleep quality are at a higher risk of poor mental health. Identifying at-risk individuals by examining sleep quality, then investigating and treating sleep problems, may improve mental health amongst farmers.